Hello :
<span>tan θ = -√3
sin</span>θ = √3/2 1/2
cosθ = -1/2
Answer:
y - 6 = -4(x+1) is equivalent to equation C: y = -4x + 2
Step-by-step explanation:
Solve the given y - 6 = -4(x+1) for y and remove the parentheses shown:
y - 6 = -4(x+1) becomes
y = -4(x + 1) + 6, or
y = -4x - 4 + 6, or
y = -4x + 2 This is equivalent to equation C.
So permiter=masure of all sides added together
so sides are(3x+2), (2x+5), and (4x)
so (3x+2)+(2x+5)+(4x)
use associative property
a+(b+c)=(a+b)+c so
(3x+2)+(2x+5)+(4x)=3x+2+2x+5+4x
group like terms becasue can move numbers around
(3x+2x+4x)+(2+5)
add like terms
(9x)+(7)
9x+7
he will use 9x+7=perimiter
Answer:
Step-by-step explanation:
Answer:
3/4
Step-by-step explanation: